2006
DOI: 10.1007/s00125-006-0251-2
|View full text |Cite
|
Sign up to set email alerts
|

Exendin-4 treatment improves metabolic control after rat islet transplantation to athymic mice with streptozotocin-induced diabetes

Abstract: Aims/hypothesis: Early islet graft survival is crucial in determining the outcome after clinical islet transplantation. Exendin-4 has anti-apoptotic and beta cell proliferative properties, which could improve islet graft survival and function. The aim of these studies was to evaluate the effect of exendin-4 on graft function after islet transplantation. Materials and methods: Rat islets were transplanted under the kidney capsule of diabetic athymic mice. First, we performed a dose-finding study and found that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 32 publications
(35 reference statements)
1
42
0
Order By: Relevance
“…Nonencapsulated islets may be injected into the liver (4,16,18,19,35,44,50,52) , kidney (5,14,15,16,17,24,27,28,32,34,35,42,46,47) , peritoneal cavity (11,35) , bone marrow (41) and subcutaneous tissue (22,48) . Ikebukuro et al (19) showed that islets and bone marrow cells, when injected into the liver using irradiation as immunosuppression, can increase the functionality of the cells for more than 365 days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonencapsulated islets may be injected into the liver (4,16,18,19,35,44,50,52) , kidney (5,14,15,16,17,24,27,28,32,34,35,42,46,47) , peritoneal cavity (11,35) , bone marrow (41) and subcutaneous tissue (22,48) . Ikebukuro et al (19) showed that islets and bone marrow cells, when injected into the liver using irradiation as immunosuppression, can increase the functionality of the cells for more than 365 days.…”
Section: Discussionmentioning
confidence: 99%
“…> 100 Lan et al (27) -> 60 Hamamoto et al (14) 2500 41 Kover et al (24) 1500 80 -120 Hiramatsu et al (17) 200 or 20 56 Socha-Urbanek et al (47) 1500 ± 200 150 Laumonier et al (28) 3000 to 3200 19.5 ± 5.8 Omer et al (35) 4000 70 Sharma et al (46) 30 30 -40 Hara et al (16) 500 to 1500 11.0 ± 2.63 Han et al …”
mentioning
confidence: 99%
“…The selective agonist to the GLP-1 receptor, Ex-4, was selected as the ligand of choice to examine GLP-1R-mediated control of food intake and gastric emptying, as this compound is used, both experimentally and clinically in the treatment of diabetes mellitus and obesity. [34][35][36][37][38] Control and chronic supracollicular decerebrate rats received Ex-4 or vehicle through IP injection or through the fourth intracerebroventricular cannula. Food intake was assessed using direct oral delivery of liquid nutrient.…”
Section: Glp-1mentioning
confidence: 99%
“…The pancreatic islets of Lewis rats (300-350 g) were isolated as previously described [30]. Briefly, the rat pancreases were digested using collagenase P solution (0.7 mg/mL; Roche Diagnostics GmbH, Mannheim, Germany) and the islets were purified using discontinuous density gradient centrifugation (Histopaque-1119, Histopaque-1077, Sigma-Aldrich).…”
Section: Pancreatic Islet Isolation and Culturementioning
confidence: 99%